PARTENOKARPI: BUAH TANPABIJI - APA, MENGAPADAN BAGAIMANA - L Agus Sukamto (Research Center for Biology-Indonesian Institute of Sciences, 2011)
Fruit growth and development occurred in plant for producing the offspring. Pollination and fertilization will form embryo and seed, which produce and supply plant growth regulators (PGR) for fruit growing. The role of seed can be exchanged with supply of POR exogenously and produce seedless fruit. Seedless fruit could be produced from triploid plant by crossing between tetraploid x diploid plants, in vitro culture of endosperm/irradiated pollen and genetic engineering or treated diploid plant by using PGR, pollen stress, chemical agent/ antibiotic and environment/ plant control. The benefit of triploid plant is quicker growth and produce of seedless fruits directly, whereas diploid plant could produce seedless fruits after fruit induction with special treatment. The other advantages of seedless fruit on certain plants are increased yield, fruit size/ weight,carotene and total sugar contents, decreased harvest period, yield fluctuation and blossom-end rot. Seedless fruit is preferential of consumer and give a higher price than the seeded fruit. Recently, seedless fruits of tomato, grape, citrus, cucumber and watermelon have been produced in commercial industries